A handbook of C1 modern English grammar (part 2): Навчальний посібник - Лопатюк, Наталія (ПВКФ "Технодрук", 2025)
This textbook contains rules and a set of exercises on the grammar of modern English, aimed at mastering the features of using non-finite verb forms: participle, gerund, infinitive. The exercises are accompanied by examples of their implementation and are correlated with the corresponding grammatical reference. The collection can also be used for self-testing of the material studied by students or for current or final control by the teacher. The manual is intended for the 2nd-year students of the Faculty of Foreign Languages ​​studying English as their 1st foreign language and the 3rd-year students studying English as their 2nd foreign language.
Keywords: non-finites; verbals; participle, gerund, infinitive